The Effect of Fruit Acids on Mature Complexion - Karčiauskaitė, Augustė Melanija; Juškutė, Deimantė; Pagojūtė, Greta; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2020)
The investigation was aimed to assess the effect of fruit acids on mature complexion. The qualitative investigation and the analysis of the case were carried out. Targeted selection was applied. Two customers wishing to undergo fruit acid procedures and improve the aesthetic condition of their mature complexion took part in the investigation. The face skin of participants was thoroughly examined, the customer card was filled in, and they were interviewed. Prior to the investigation, skin phototype 2–3, problem areas of pigment spots and rash elements on the cheeks and the forehead, as well as dilated capillaries (telangiectasias) were determined. Most of the skin care products containing vitamin C were applied to the younger customer. Products inducing several effects (containing fruit extracts glycol, orange acids) were applied to the older customer. Changes in the condition of mature skin were determined in both cases of the procedures applied. Pores shrank faster, skin turgor increased, the skin greasiness decreased in younger customer (X1). Visually identifiable changes in the older customer (X2) were determined after the cycle of all the procedures had been completed: the area below the eyes and pigment spots brightened, pores and capillary network shrank, number of comedones decreased, and skin became more elastic. Combined skin care products applied to decrease pigment spots and the capillary network made the greatest effect on the change in the skin. Micellar water and lotions produced the minimal effect on changes in skin texture.